Determinants and contextual barriers of childhood stunting in rural Indonesia: a mixed-methods study in Sengonwetan Village - Fadhilah Apriliandri; Danny Yovita Maharani; Amelina Ratih Listyaningrum (Berita Kedokteran Masyarakat, 2026)
Purpose: Stunting continues to pose a significant child health burden in Indonesia, particularly in rural settings where healthcare access, maternal education, and dietary quality remain limited. Addressing these community-level determinants is crucial to accelerating progress in reducing stunting. This study aimed to identify the determinants and explore contextual barriers of childhood stunting among children under five in Sengonwetan Village, Grobogan Regency, Indonesia. Methods: A mixed-methods cross-sectional study was conducted in March 2025 involving 120 children aged 6–59 months selected through stratified random sampling. Anthropometric measurements followed World Health Organization standards. Household food security, dietary diversity, and maternal characteristics were assessed using structured questionnaires, while qualitative interviews explored contextual barriers. Quantitative data were analyzed using logistic regression, and qualitative data were analyzed thematically. Results: Stunting prevalence was 21.7%. Children of mothers with lower education had higher odds of being stunted (AOR 2.10; 95% CI 1.05–4.20). Household food insecurity (AOR 1.80; 95% CI 1.02–3.22) and low dietary diversity (AOR 1.95; 95% CI 1.10–3.48) were also associated with increased odds of stunting. Recurrent diarrheal episodes emerged as the strongest determinant (AOR 3.20; 95% CI 1.30–7.85). Qualitative findings highlighted limited dietary diversity, economic constraints, and inadequate sanitation as key contextual barriers. Conclusion: Childhood stunting in this rural setting is influenced by both measurable determinants and contextual barriers, particularly maternal education, household food security, dietary diversity, and recurrent infections. Integrated, community-based interventions that address both behavioral and structural factors are essential to accelerate reductions in stunting.